GAMBARAN KOMUNIKASI GURU DENGAN ORANG TUA DALAM MEMBENTUK KARAKTER SISWA DI SDIT GHILMANI KETINTANG SURABAYA - M. Ainur Roziqin; Nafiah Nafiah; Sri Hartatik; Mohammad Taufiq (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The purpose of this study are to describe the communication between teachers and parents in building the character of students at SDIT Ghilmani Ketintang Surabaya and to determine the impact of such communication. The research method used was descriptive qualitative, then data collection techniques used were interviews, observation, and documentation. The data analysis techniques used were data condensation, data display, and data verification which were validated by using the credibility test and the dependability test. The results of this study indicated that the picture of teacher and parent communication in building the character of students was as follows: 1) class groups created through social media such as whatsapp and so on, 2) communication through anecdot records or anecdotal notes used to record student behavior every day at school, the note was submitted to the parents of students when receiving report cards, 3) Communication through information books, and independent student communication, 4) home visit activities, namely teacher visited to student homes, to match the development of student behavior at school , 5) perenting activities, namely activities to bring in psychologists to provide direction to parents on how to properly educate children. The impacts of communication between teachers and parents were: 1) good cooperation between teachers and parents in building the character of students at home and at school, 2) there was a change in student character, because every day is monitored through information books, and independent student communication , 3) to increase parental knowledge on how to educate children well through parenting activities, 4) student achievement increased because all student activities were monitored through anecdote record . Recommendations from this study were 1) the results of this study can be used by schools, teachers, parents to carry out communication so as to improve the character of students at school and at home by intensifying their communication so that the character of students is built in accordance with the expectations and goals of teachers and parents, 2) other researchers can use as a reference for conducting similar research related to teacher and parent communication in building student character.